Rate And Quantity of Vine Fertilizer - Ochildiev Utkir Ollanazarovich (Genius Publishing Group, 2021)
Depending on the duration and quantity of organic and mineral fertilizers, they are divided into basic and additional fertilizers. In autumn and early spring, the main fertilizer is introduced to provide plants with nutrition throughout the growing season. During fertilization, additional fertilizers are introduced in small amounts to supplement the nutritional needs of the plants at the right time. Their importance will be greatly increased if basic fertilizers are found in the vineyard. In the fall, a mixture of manure, compost, phosphorus or phosphorus-potassium fertilizers, ground phosphate rock, and engravings is used in the vineyard. Potash fertilizers are usually used simultaneously with phosphorus fertilizers. Most organic and mineral fertilizers add 40-60 cm to the depth of the bulk of the absorbing roots
Keywords: Grapes; variety; bush; trellis